Sorption of lead on cementitious materials in presence of organics - Drtinová, Barbora; Kittnerová, Jana; Bergelová, Karolína; Burešová, Marta; Baborová, Lucie (Frontiers in Nuclear Engineering, 2023)
Commercial cementitious material, hydrated cement pastes of type CEM I and CEM III, and a synthetic cementitious phase CSH (calcium-silicate-hydrates) with a Ca/Si ratio equal to 1.0, 1.2, and 1.4 were used in the study of lead sorption. Kinetic and equilibrium experiments were performed under different conditions, namely liquid to solid phase ratio, the presence of organic compounds (EDTA, phthalate), and also temperature. The duration of equilibrium experiments was determined based on kinetic experiments, 1 week for CSH and 3 weeks for HCP. Equilibrium experiments were evaluated using the distribution ratio Rd and the sorption isotherms. For both hydrated cement pastes, Rd’s in the range 102 103 L kg 1were found while for CSH the distribution ratio values were an order of magnitude higher under comparable conditions. The difference in the studied cementitious materials was also manifested in the shape of the sorption isotherm, while the behavior of CSH can be fitted linearly and therefore by the Kd model, for HCP as more complex cement material it is necessary to use a nonlinear isotherm description. The effect of organic matter, represented here by EDTA and phthalate, described by the sorption reduction factor SRF was more apparent for CSH, where its value was always higher than 1 and reached up to 500. On the contrary, for HCP CEM I and CEM III, all determined SRFs were less than 1.